Using normalized equations to solve the indetermination problem in the Oaxaca-Blinder decomposition: an application to the gender wage gap in Brazil - Scorzafave,Luiz Guilherme (2007)
There are hundreds of works that implement the Oaxaca-Blinder decomposition. However, this decomposition is not invariant to the choice of reference group when dummy variables are used. This paper applies the solution proposed by Yun (005a,b) for this identification problem to Brazilian gender wage gap estimation. Our principal finding is the increasing difference in part-time work coefficients between men and women, which contributes to narrow the gender wage gap. Other studies in Brazil not using any correction of the identification problem have found different results.